Theoretical Views On Poetic Motive - Khakimjonova Ra’no Olimjon qizi (Journal of Artificial Intelligence and Digital Economy, 2024)
This article focuses on the literary assimilation and theoretical interpretations of the term motif, the relationship between motive and image as well as the tropical types of motif, which differ from symbol, metaphor and similar features.